(untitled) (Journal of Asian Development Studies, 2024)
The following research mainly focuses on the inheritance rights of women in Upper Chitral. In Pakistani society, women are discriminated against and have not always been subjected to decent behavior. Their rights should be addressed in various facets of life, such as when deciding their roles and choosing their marriage partners. This research will look into the religious and constitutional laws regarding inheritance and their implementation; it will give the readers an idea of whether women in Upper Chitral are aware of their rights related to inheritance and if they still need to be made aware. It will also highlight the common causes of their need for more awareness. Further research will elaborate on the patriarchal mindset prevailing in Upper Chitral that is hindering women’s independence and growth. A qualitative approach has been used for this research. In-depth interviews were conducted to get the relevant data. Purposive sampling was employed. Primary data has been used for this research. The study found that women in Upper Chitral inherit significantly less than men, limiting their economic opportunities and enhancing the gender gap. Cultural traditions often clash with legal frameworks designed to promote equality. However, there are positive improvements as evolving social norms, increased legal awareness, and community initiatives are challenging these discriminatory practices. Younger generations are more flexible to gender equality. Education empowers women to fight for their inheritance rights. The study recommends a multi-pronged approach that addresses legal reforms, cultural beliefs, and economic empowerment through education and financial literacy.